Pengukuran Kinerja Saham Melalui Likuiditas Pada Saham JII 70 (International Forum of Researchers and Lecturers, 2024)
The main objective of this study is to examine the impact of investment on stock performance both directly and by using the role of liquidity. The population of shares included in JII70 for the 2019-2022 period, using purposive sampling, obtained 38 shares that met the criteria, thus there were 152 data used in testing, using the MRA analysis tool. The test results showed that investment had a significant direct impact on improving stock performance, and was also further strengthened by liquidity.